2020
DOI: 10.21315/mjms2020.27.3.8
|View full text |Cite
|
Sign up to set email alerts
|

The Predictor Role of Perceived Social Support and Spiritual Intelligence in Hope Among Thalassemia Patients

Abstract: Background Thalassemia is a prevalent chronic blood disorder, which is accompanied with a wide range of challenges. This study aimed to determine the predictor role of perceived social support and spiritual intelligence in hope among thalassemia patients. Methods This cross-sectional study was conducted on 300 thalassemia patients. The data were collected using Miller hope scale, spiritual intelligence scale, and personal resource questionnaire. The data were analysed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In healthcare, some researchers, most of them in Iran, have tried to develop SI as way to help people cope with existential challenges. For example, two independent studies (Hosseinpour et al 2020;Pasyar et al 2020) showed that training in Spiritual Intelligence and subsequent assessment using Amram and Dryer's (2008) ISIS and King's SISRI-24 (King and DeCicco 2009), respectively, have a positive effect on hope and life expectancy among the chronically ill. Others have trained care providers in SI to work with patients. Riahi et al (2018) found that SI training improved nurses' competence in spiritual care in critical care units, which in turn improved patient quality of life.…”
Section: Developing Spiritual Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…In healthcare, some researchers, most of them in Iran, have tried to develop SI as way to help people cope with existential challenges. For example, two independent studies (Hosseinpour et al 2020;Pasyar et al 2020) showed that training in Spiritual Intelligence and subsequent assessment using Amram and Dryer's (2008) ISIS and King's SISRI-24 (King and DeCicco 2009), respectively, have a positive effect on hope and life expectancy among the chronically ill. Others have trained care providers in SI to work with patients. Riahi et al (2018) found that SI training improved nurses' competence in spiritual care in critical care units, which in turn improved patient quality of life.…”
Section: Developing Spiritual Intelligencementioning
confidence: 99%
“…SI, while an innate capacity, is one that, like any other intelligence, can be cultivated (e.g., Charkhabi et al 2014;Heydari et al 2017Heydari et al , 2018Hosseinpour et al 2020). Importantly, as an intelligence, SI has been shown in numerous studies to be associated with and to predict various positive outcomes cross-culturally (e.g., Amirian and Fazilat-Pour 2016;Khosravi and Nikmanesh 2014;Kaur et al 2015;Mansouri et al 2016;Pant and Srivastava 2019;Pasyar et al 2020). Finally, research has shown that aspects of SI are reliant on the use and development of certain neurological networks in the brain, analogous to the ways in which mathematical and linguistic intelligences are associated with certain brain areas (e.g., Hyde 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Somasundaram et al has also shown that perceived social support has a positive effect on emotional well-being and reducing feelings of hopelessness [ 27 ]. Perceived social support enables individuals to achieve their dreams by providing positive impact, a sense of predictability, stability in life situations and promoting well-being [ 28 ], however, lack of perceived social support may lead to feelings of hopelessness. In addition, the basic condition for the establishment of hope is to obtain the encouragement and support of others, and when individuals get the support, they will be motivated to voluntarily achieve the goal [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a complicated process of thoughts, emotions, and functions that change over time and facilitates the achievement of goals and outcomes in future [ 11 ]. Evidence has also indicated that hope is related to excellence, acceptance of compatibility [ 11 ], depression, mental health, religious beliefs [ 12 ], and spirituality [ 13 ]. Furthermore, social support and relationship with others have been found to be effective in facilitation and maintenance of hope [ 14 ].…”
Section: Introductionmentioning
confidence: 99%